Eye on the world : a life in international service - Quainton, Anthony C. E. (ADST-DACOR Diplomats and diplomacy series, 2022)
"The autobiography of one of America's highly esteemed diplomats, Ambassador Anthony "Tony" C. E. Quainton, and his long and storied career in eleven countries on six continents in a unique diversity of top posts"--